An Analysis Behaviour Of Palm Sugar Traders In Mandailing Natal Based On Islamic Business Ethics Perspective: Analisis Perilaku Pedagang Gula Aren Di Mandailing Natal Berdasarkan Prespektif Etika Bisnis Islam - Finik Kharianti; Nur Ahmadi Bi Rahman (Journal of Indonesian Management, 2022)
Trade as one of the economic activities carried out by most people in Indonesia. Indonesia has various natural potentials both in agriculture and animal husbandry. One of the advantages that Indonesia has is soil fertility so that it can have a positive impact in the form of the growth of various plants, one of which is palm trees. The output of processed palm trees is arena sugar which is widely used by the community for daily food. In addition, palm sugar is also one of the leading commodities in Mandailing Natal, North Sumatra. The purpose of this study was to analyze the behavior of palm sugar traders in Mandailing Natal based on the perspective of Islamic business ethics. The research method used is a qualitative method with a descriptive approach. The results of this study indicate that the behavior of palm sugar traders in Mandailing Natal is in accordance with Islamic law and Islamic business ethics.